2012
DOI: 10.1371/journal.pone.0050166
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant Human Cytomegalovirus (HCMV) RL13 Binds Human Immunoglobulin G Fc

Abstract: The human cytomegalovirus (HCMV) protein RL13 has recently been described to be present in all primary isolates but rapidly mutated in culture adapted viruses. Although these data suggest a crucial role for this gene product in HCMV primary infection, no function has so far been assigned to this protein. Working with RL13 expressed in isolation in transfected human epithelial cells, we demonstrated that recombinant RL13 from the clinical HCMV isolates TR and Merlin have selective human immunoglobulin (Ig)-bind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
64
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(65 citation statements)
references
References 41 publications
(57 reference statements)
1
64
0
Order By: Relevance
“…While variability in RL11 genes was described previously, analyses of the most variable members, RL5A, RL6, RL12, and RL13, were limited to a comparison of seven strains (Table 2). Especially for the RL13 gene, it would be of interest to study the functional behavior of different variants, as this gene has been implicated as a growth temperance factor (72) and in immunomodulation (73). Considering the latter function of RL13, we found that the endocytic YxxL motif essential for internalization of IgGs was 100% conserved among clinical isolates.…”
Section: Resultsmentioning
confidence: 90%
“…While variability in RL11 genes was described previously, analyses of the most variable members, RL5A, RL6, RL12, and RL13, were limited to a comparison of seven strains (Table 2). Especially for the RL13 gene, it would be of interest to study the functional behavior of different variants, as this gene has been implicated as a growth temperance factor (72) and in immunomodulation (73). Considering the latter function of RL13, we found that the endocytic YxxL motif essential for internalization of IgGs was 100% conserved among clinical isolates.…”
Section: Resultsmentioning
confidence: 90%
“…Eight of the identified glycoproteins, RL11, RL12, UL4, UL5, UL7, UL8, UL10, and UL11, are members of the RL11 multigene family of HCMV proteins (60). Two of them, RL11 and RL12, are known to bind human IgG (61,62). O-Glycosites mainly localized to either the very N terminus or the juxtamembrane stem region of the RL11 family members and not the characteristic RL11D domain (Fig.…”
Section: Mapping O-glycosites In Human Herpesvirusesmentioning
confidence: 99%
“…In the case of HCMV gp68, the cotrafficking of the viral Fc␥R to lysosomes together with the IgG-antigen complex should also result in degradation of the receptor, whereas dissociation of gE-gI from the IgG-antigen complex prior to entering lysosomes would allow gE-gI to be recycled back to the cell surface. The postulated differences in trafficking resulting in degradation of gp68, but not gE-gI, may reflect the fact that HCMV expresses at least three different IgG Fc binding proteins (3,13,14), compared with HSV-1, which expresses only one known Fc␥R (5, 11). For both viruses, internalization of ABB complexes and consequent degradation would enable clearance of membrane proteins that serve as antigenic targets and selective removal of antiviral antibodies, The funders had no role in study design, data collection and analysis, decision to publish, or preparation of the manuscript.…”
Section: Fig 1 Schematic Diagrams Of Abb and Non-abb Complexes At A Cmentioning
confidence: 99%
“…ABB protects virally infected cells from antibodyand complement-dependent neutralization (10), antibody-dependent cell-mediated cytotoxicity (11), and granulocyte attachment (12). The HCMV glycoproteins gp68, gp34, Toll-like receptor 12 (TLR12), and TLR13 act as Fc␥Rs to bind human IgG (3,6,13,14). Recent studies reported formation of ABB complexes with gp68 and with gp34 and demonstrated their functional importance by showing that cells infected with HCMV lacking gp68 and/or gp34 triggered stronger activation of the host Fc␥Rs and NK cells than cells infected with wildtype HCMV (15).…”
mentioning
confidence: 99%